The classroom pre-test-post-test control of STEM worksheet: The validation on physics subject learning for junior high school students in Martapura City, South Kalimantan - Rifâ€™ah Radhiyati; Arif Sholahuddin; Suyidno Suyidno (Master Program of Natural Science Education, Universitas Lambung Mangkurat, 2024)
The impact of a STEM-based worksheet on the learning outcomes of 7th grade junior high school students in Martapura City, South Kalimantan, Indonesia, is investigated. The study describes the development and validation of a worksheet on the topic of energy in living systems with the objectives are to create a STEM-based worksheet and then applying it directly to 7th grade students in South Kalimantan. Direct observation was conducted as an evaluation to determine the effectiveness of the STEM approach on student learning outcomes using pre-test-post-test analysis. The results show aspect of â€œThere is a table of contents and instructions for use that are easy to learnâ€ has the highest percentage in the feasibility of components and content suitability of 93.3%, while in the language aspect, the highest percentage of 80.0% is in the use of appropriate and correct Physics terms and effective language and in accordance with the ability level of students. In the presentation aspect, the highest percentage of 86.7% is found in the coherent order of presentation and clear and detailed activity objectives, while in the graphic aspect, the highest percentage of 86.7% is found in the cover illustration that is attractive and illustrates the content/material in the worksheet. In contrast, the lowest percentage of 73.3% was found in several aspects, such as the suitability of worksheet content to the abilities and needs of students, the effectiveness of the language used, the presentation of problems and activities in accordance with the material, and graphical aspects such as an attractive general appearance, neat and consistent layout, clear illustrations/images, and attractive appearance design.